STUDI MULTIKASUS: EPIDEMI PERILAKU MEROKOK Dl KALANGAN REMAJA DAN IMPLIKASINYA DALAM PENDIDIKAN - Mohammad Efendi (Jurnal Ilmiah Visi, 2006)
The purpose of this study is to describe smoking behavior of youth. The methods are quatitative, and a multiple case study. Data gathered in the study show that smoking behavior performed by youth has reached a critical level. The Determinant factor influencing their behavior is social environment, such as school, family, and society. Based on findings, it is neglected that education insitution either formal or informal, and youth organizations do serious efforts to minimize smoking behavior. Also, they should run a continous program to promote healthy life among youth.